Optimizing Company Performance through Segmented Reporting, Investment Center Evaluation, and Pricing Strategy - Sabiq, Zamzami Sabiq; Agrenawan, Domas; Auliaur, Razin; Sugianto, Aan; Audrey, Pramudya (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
In an increasingly dynamic and competitive business environment, companies are required not only to survive, but also to continue to innovate and improve performance. This study examines the simultaneous influence of segmented reporting, investment center evaluation, and pricing strategy on the performance of companies in the manufacturing sector listed on the Indonesia Stock Exchange during the period 2020 to 2024. With a quantitative-explanatory approach and multiple linear regression analysis, company performance is measured through Return on Investment (ROI) and Net Profit Margin (NPM). The results of the study show that the three independent variables have a significant effect on financial performance, with investment center evaluation having the strongest influence, followed by segmented reporting and pricing strategy. The integration of these three elements supports a more effective strategic management system, strengthens accountability, and increases profitability. This study contributes to the development of a more comprehensive and applicable strategic management accounting system to support sustainable business growth.